Analisis Pendapatan Dan Strategi Pengembangan Usaha Ikan Bandeng Tanpa Duri Di Desa Lalombi Kabupaten Donggala Income Analysis and Development Strategy of Processed Milkfish in Lalombi Village of Donggala District - Eka Aji Pramita; Saiful Darman; Hadayani Hadayani (Universitas Tadulako, 2018)
ABSTRACT This study aimed to determine the level of income of processed milkfish businesses and their development strategy in Lalombi village. Data obtained was gathered through observation, interview, and focus group discusion (FGD). Respondents in this study included all units of processed milkfish business population taken through census method, four people from Marine and Fishery Office of Donggala district of Central Sulawesi Province, the head of Lalombi Village, and an extension worker, a traditional leader. The result of income analysis of the milkfish business in Lalombi village was IDR 1,116,960/month with the R/C Ratio of 1.77 indicating that the milkfish business is very profitable and feasible to be developed. The result of the SWOT analysis shows that the strategy of milkfish business development in Lalombi village is positioned in the third quadrant supporting WO (Weaknesses-Opportunities) strategy or turnaround strategy. The strategies included such programs as (1) increasing amount of production to meet relatively high demand and (2) optimizing the government support (cultivation, package assistance, counseling, and capital). The QSPM analysis showed that the best program that could be applied to implemented the strategy was the second program